2023
DOI: 10.1038/s41598-023-29809-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of the speckle imaging sub-pixel correlation analysis in revealing a mechanism of microbial colony growth

Abstract: The microbial colony growth is driven by the activity of the cells located on the edges of the colony. However, this process is not visible unless specific staining or cross-sectioning of the colony is done. Speckle imaging technology is a non-invasive method that allows visualization of the zones of increased microbial activity within the colony. In this study, the laser speckle imaging technique was used to record the growth of the microbial colonies. This method was tested on three different microorganisms:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…An increase of signal values represents spatiotemporal activity patterns during colony growth ( Balmages et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase of signal values represents spatiotemporal activity patterns during colony growth ( Balmages et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies using a non-contact optical technique called laser speckle contrast imaging, we determined bacterial growth after 3 h from the beginning of activity ( Balmages et al, 2021b ). In our microbiology experiments performed on solid media the term “activity” refers to a wide range of environmental changes including bacteria doubling, surface roughness changes caused by colony growth, as well as fluctuations of optical properties of the media caused by bacteria growing process ( Balmages et al, 2023 ). A laser speckle is an interference pattern produced by coherent light reflected from an illuminated rough surface.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, sub-pixel correlation analysis in speckle imaging is a new frontier for this task. 12 At the same time, the detection of bacterial colonies using neural networks is a promising approach 13,14 . However, when the aim is only to detect and count bacterial colonies, it is not necessary for the colony identifying feature (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of these approaches is that objects in the image that are not colonies (e.g., pieces of the wall of a Petri dish, air bubbles) may also appear in the result as colonies [ 12 ]. More recently, the potential of laser speckle imaging (LSI) for the study of bacterial colony growth has been demonstrated by Balmages et al [ 13 ]. This approach allows the identification of pixels in images of cultures that do not change over time and those that do, using the laser as a coherent light source.…”
Section: Introductionmentioning
confidence: 99%